Diagenesis and reservoir quality evolution of the Lower Cretaceous turbidite sandstones of the Agat Formation (Norwegian North Sea): Impact of clay grain coating and carbonate cement. (August 2022) - Azzam, Fares; Blaise, Thomas; Patrier, Patricia; Elmola, Ahmed Abd; Beaufort, Daniel; Portier, Eric; Brigaud, Benjamin; Barbarand, Jocelyn; Clerc, Sylvain
Abstract: The turbidite sandstone of the Agat Formation is one of the most important hydrocarbon reservoirs in the Lower Cretaceous succession of the Norwegian North Sea. The diagenetic history of these sandstones has greatly impacted the reservoir quality, resulting in a high heterogeneity in porosity and permeability. To investigate this impact, sixty thin sections and rock samples were investigated through petrographic observations, geochemical microanalysis, and X-ray diffraction. Three main diagenetic events occurred during burial and influenced the reservoir properties: (1) mutual growth of chlorite, siderite, and apatite, (2) calcite cementation, and (3) dissolution of K-feldspar and calcite. Early diagenesis occurs under strongly reducing conditions, leading to the formation of Fe-chlorite/berthierine, siderite, pyrite, and apatite forming coatings around the detrital grains. Chlorite coatings have a key role in controlling the reservoir quality in the Agat Formation. In the lower part of the reservoir, chlorite forms thick coats (15–25 μm) that strongly reduce permeability. Conversely, in the upper part of the reservoir, chlorite coats are thinner (4–10 μm), favoring porosity preservation by inhibiting quartz overgrowth. X-ray diffraction and electron microscope observations indicate Fe-rich chlorite of Ib polytype, suggesting solid-state transformation from a berthierine precursor. The kinetics of berthierine/chlorite growth are governed by the dissolution of Fe-rich grains and fine fraction materials found as matrix and early coats. These grains are abundant in the lower part of the reservoir favoring the formation of thick chlorite coats. Chlorite was followed by pervasive calcite cementation in deep burial conditions creating low permeability barriers in the reservoir. The source of this calcite is internal and probably related to the dissolution of an early diagenetic calcite cement forming at shallow depth, with a minor contribution from marine carbonates. During late diagenesis, K-feldspar grains and calcite cements underwent intense dissolution creating secondary porosity and consequently increasing permeability. The input of acidic fluids associated with the maturation of the source rocks could have facilitated these dissolution reactions. Our results highlight the importance of inherited mineralogy in controlling the distribution of chlorite, carbonates, and secondary porosity in the Agat Formation. This study provides useful indicators to help predict diagenetic reactions that can occur in deep marine siliciclastic reservoirs. Highlights: The Agat Formation experienced a complex and multistage diagenetic history. Thick-authigenic chlorite coats caused significant porosity loss in the reservoir. Chlorite formed through solid-state transformation from a berthierine precursor. Intense dissolution of feldspars and calcite cement improved the reservoir quality. Initial mineralogical composition mainly controlled the diagenetic processes evolution.